Service Quality Assessment of Library at an Educational Tourism Institution - Subaşı, Elif (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Today, within the framework of the rapidly growing education tourism in Northern Cyprus, many universities, especially Eastern Mediterranean University, enable education services to students who come from various countries of the world; and we can say that libraries have the biggest role among all service units within these institutions. Providing information and documents to its users, EMU, Özay Oral Central Library carries the risk of falling short in terms of quality in today's changing conditions. For this reason, we felt the need to measure and evaluate the library's service quality level from the users' point of view by choosing a suitable method. Consequently, we obtained quantitative valid and reliable data from 285 target participants with an online-based Likert-scale survey that helped us to make proper analyzes. Of this number, 165 are men and 120 are women, the largest number in terms of positions (117) here are undergraduate students, then graduate and doctoral students with the participation of 107, and the rest are academic staff. All details of this study are indicated in the "data analysis and findings" chapter of the thesis with various tables and figures. However, to summarize, the average score values of the "General Results" shown in Table 5 and Figure 5, respectively; the first seems to be related to the attitude and behavior of the best service personnel towards them. Second, it concerns whether the library provides the useful and necessary information to users in their academic work. The third is for the entire library service quality, which is evaluated in a holistic framework. The overall service quality of the Library is better than the average score value of other specific services, although it remains slightly below user expectation in terms of competence. Keywords: educational tourism, Edu-tourist, customer satisfaction, student satisfaction, service quality, library service quality

ÖZ: Günümüzde, Kuzey Kıbrıs'ta hızla büyüyen eğitim turizmi çerçevesinde başta Doğu Akdeniz Üniversitesi olmak üzere bir çok üniversitemiz Dünyanın çeşitli ülkelerinden gelen öğrencilere eğitim hizmeti vermektedir; ve bu kurumların bünyesinde olan tüm hizmet birimleri içerisinden en büyük role sahip kütüphanelerin olduğunu söyleyebiliriz. Kullanıcılarına bilgi ve belge sağlayan DAÜ, Özay Oral Merkez Kütüphanesi, günümüz değişen koşullarında kalite anlamında yetersiz kalma riski taşımaktadır. Bu nedenle, uygun bir yöntem seçerek kurumun hizmet kalitesi düzeyini kullanıcıların bakış açısından ölçme ve değerlendirme gereğini duyduk. Bunun sonucunda, uygun analizler yapmamıza yardımcı olan çevrimiçi tabanlı Likert ölçekli bir anketle 285 hedef katılımcıdan (kütüphane kullanıcıları) nicel, geçerli ve güvenilir veriler elde ettik. Bu rakamın 165'i erkek, 120'si ise kadın olmak üzere pozisyon açısından en büyük rakamla (117) burada lisans öğrencileri, daha sonra 107 kişinin katılımıyla birlikte yüksek lisans ve doktora öğrencileri, geri kalanı ise akademik kadrodan oluşan katılımcılardır. Bu çalışmanın tüm detayları çeşitli tablo ve şekillerle tezin "veri analizi ve bulgular" bölümünde belirtilmiştir. Ancak özetlemek gerekirse, Tablo 5 ve Şekil 5'te gösterilen “Genel Sonuçların” ortalama puan değerleri sırasıyla; birincisi, en iyi hizmeti veren personelin onlara karşı tutumu ve davranışıyla ilgili görünmektedir. İkincisi, tüm kütüphanelerin bunun için yaratılmasının ana sebebi olan Kütüphanenin, akademik çalışmalarında kullanıcılara faydalı ve gerekli bilgiler sağlayıp sağlamadığıyla ilgilidir. Üçüncüsü ise, bütünsel bir çerçevede değerlendirilen tüm kütüphane hizmet kalitesi içindir. Yeterlilik anlamında bile kullanıcı beklentisinin biraz altında kalmasına rağmen, Kütüphanenin genel hizmet kalitesi ortalama puan değeri diğer spesifik hizmetlere göre daha iyi bir düzeyde görülmektedir. Anahtar Kelimeler: eğitim turizmi, Eğitim-turisti, müşteri memnuniyeti, öğrenci memnuniyeti, hizmet kalitesi, kütüphane hizmet kalitesi
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Co-Supervisor: Prof. Dr. Ali Öztüren, Supervisor: Prof. Dr. Turgay Avcı.
Keywords: Tourism; Academic libraries--Quality--Evaluation; Özay Oral Library--University Library--Evaluation--Student Satisfaction--User Satisfaction--Eastern Mediterranean University--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Education Tourism--Library Services--Cyprus, North; Academic Tourism; Tourism--Education (Higher) Cyprus (Turkish Republic of Northern Cyprus, 1983-); Students, Foreign--Education (Higher); University Information services--Library Services--Service Quality Measures; Educational tourism; Edu-tourist; customer satisfaction; student satisfaction; service quality; library service quality